2008
DOI: 10.1007/s10750-008-9410-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydroelectricity and fish: a synopsis of comprehensive studies of upstream and downstream passage of anadromous wild Atlantic salmon, Salmo salar, on the Exploits River, Canada

Abstract: Government (Fisheries and Oceans Canada) and industry (Abitibi Consolidated Company of Canada) have been working cooperatively to protect and enhance wild Atlantic salmon populations on the Exploits River, insular Newfoundland, Canada. Since the mid-1960s, enhancement programmes and construction of fish passage facilities at natural and man-made barriers in the watershed have expanded the range and increased the returning adult population from 1200 fish (circa 1960) to 22,000 fish, on average. Since 1997, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…It has been suggested that the use of screening systems (Scruton et al , 2008) and strobe lights (Johnson et al , 2005) can guide or scare fishes away from intakes. Thus, in 2008 a floating boom was introduced in front of the intake tunnel and one submerged strobe light on each side of the tunnel entrance, both facing upstream towards a point in the middle of the intake flow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the use of screening systems (Scruton et al , 2008) and strobe lights (Johnson et al , 2005) can guide or scare fishes away from intakes. Thus, in 2008 a floating boom was introduced in front of the intake tunnel and one submerged strobe light on each side of the tunnel entrance, both facing upstream towards a point in the middle of the intake flow.…”
Section: Methodsmentioning
confidence: 99%
“…Re‐establishment of migration routes is essential to re‐introduce or enhance these populations across their distribution areas. While research and implementation of upstream migration solutions is extensive, and indeed often successful (Scruton et al , 2008), seaward migration of juveniles (smolts) remains a major challenge in many river systems. Salmonid smolts are small and numerous, and they appear to follow the main discharge (Rivinoja, 2005) often leading them into the hydropower intake and turbines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once dispersers enter the forebay, downstream passage efficiency will then be determined by the ability to locate and enter turbine entrances, which can be estimated using FEZ Entry p . We are beginning to learn more about the forebay and reservoir hydraulic conditions that promote guidance for out‐migrating anadromous species (Enders, Gessel, & Williams, ; Kemp, Gessel, & Williams, ; Scruton, McKinley, Kouwen, Eddy, & Booth, ; Scruton et al., ). In general, increased velocities tend to promote guidance for anadromous salmonids.…”
Section: Conceptual Model Of Downstream Passage Efficiency For Fish Pmentioning
confidence: 99%
“…Additionally, due to disregard of environmental consequences, partly due to unawareness, river habitats have been seriously degraded by alterations to water clarity and temperature as well as species abundance and diversity (Schilt ; Scruton et al . ).…”
Section: Introductionmentioning
confidence: 97%